Effervescent Powder Activity of the God’s Crown Fruit Extract (Phaleria macrocapa) (Scheff) Boerl) in Rats Model of Alloxan-Induced Balb/C Diabetes Mellitus - Cendekiawan, Khrisna Agung; Lia Fitriyaningrum (HM Publisher, 2023)
God's crown fruit (Phaleria macrocarpa (Scheff) Boerl) is one of the ingredients that can be used as a natural anti-diabetic because of the presence of flavonoids which have activity as antioxidants. This study aimed to determine the anti-diabetic activity of the powder-effervescent God's crown fruit extract in various doses in test animals and to determine the effective dose of the powder-effervescent God's crown fruit extract as an anti-diabetic. This study is an in vivo experimental study. This study used 25 rats (Mus musculus) Balb/c, which were grouped into 5 groups (negative control, positive, and 3 treatment groups). Rats were induced diabetes mellitus with alloxan, then blood glucose levels were assessed. Data analysis was carried out using SPSS software version 25 in univariate and bivariate. There was no significant effect on reducing blood glucose levels in mice treated with effervescent powder of God's crown fruit extract.